2005
DOI: 10.1007/s10238-005-0069-0
|View full text |Cite
|
Sign up to set email alerts
|

HLA DR/DQ alleles and risk of type I diabetes in childhood: a population–based case–control study

Abstract: The objective was to evaluate HLA DR/DQ alleles and their risk factor for type 1 diabetes in the Abruzzo region (central Italy). Sixty incident cases from the Abruzzo region were studied together with 120 unrelated control subjects living in the same administrative areas. The relative risk of diabetes associated with the alleles under study was calculated by deriving the odds ratio (OR) maximum likelihood estimates and their 95% confidence intervals (CI) by the exponentiation of the logistic regression beta-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
4
14
1
Order By: Relevance
“…In this study, there was a strong association of the heterozygote DQ2/DQ8 (38.8%, OR ϭ 18.4) and DR3/DR4 (32%, OR ϭ 13.7) with T1DM; this agrees with findings in other Arab populations, such as Kuwaitis [29] and Egyptians [30], as well as in non-Arabs, such as in Spanish [31], Greeks [32], British [33], and Italians [34].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, there was a strong association of the heterozygote DQ2/DQ8 (38.8%, OR ϭ 18.4) and DR3/DR4 (32%, OR ϭ 13.7) with T1DM; this agrees with findings in other Arab populations, such as Kuwaitis [29] and Egyptians [30], as well as in non-Arabs, such as in Spanish [31], Greeks [32], British [33], and Italians [34].…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, this pocket in DQ2, DQ8 and DQ8.2 molecules has been reported to be similar, suggesting no importance in determining susceptibility to diabetes [88,89]. Several studies have reported an increased occurrence of DQ8 in patients of Caucasian origin [78,82,90].…”
Section: Mhcmentioning
confidence: 93%
“…In addition, DQ2 (DQB1*0201-DQA1*0501) and DQ8 (DQB1*0302-DQA1*0301), which occur in strong linkage disequilibrium with DR3 and DR4, respectively, are strongly associated with the disease in several Caucasian populations, especially when present in the DR3/DR4 heterozygous condition [78][79][80][81][82][83]. It has been suggested that DR3/DR4 heterozygosity exerts a synergistic effect and provides a much greater risk to T1D than DR3 homozygosity in most populations.…”
Section: Mhcmentioning
confidence: 97%
See 1 more Smart Citation
“…To the best of our knowledge, the present study is the first to identify a positive association between HLA-DQB1*0202 and T1D (Table 2). DQB1*0201 and DQB1*0302 were positively associated with T1D in various ethnic populations including Asians [34,35] , European [36][37][38][39][40][41][42][43] , and Americans [44][45][46] . Similar results were reported for Arab patients from Saudi Arabia [47,48] , Kuwait [49] , Tunisia [50] , Lebanon [51] , and Israeli [52] .…”
Section: Discussionmentioning
confidence: 99%